UBF complexes with phosphatidylinositol 4,5-bisphosphate in nucleolar organizer regions regardless of ongoing RNA polymerase I activity - Sobol, Margarita; Yildirim, Sukriye; Philimonenko, Vlada V; Marášek, Pavel; Castaño, Enrique; Hozák, Pavel (Nucleus (Austin, Tex.), 2013)
To maintain growth and division, cells require a large-scale production of rRNAs which occurs in the nucleolus. Recently, we have shown the interaction of nucleolar phosphatidylinositol 4,5-bisphosphate (PIP2) with proteins involved in rRNA transcription and processing, namely RNA polymerase I (Pol I), UBF, and fibrillarin. Here we extend the study by investigating transcription-related localization of PIP2 in regards to transcription and processing complexes of Pol I. To achieve this, we used either physiological inhibition of transcription during mitosis or inhibition by treatment the cells with actinomycin D (AMD) or 5,6-dichloro-1β-d-ribofuranosyl-benzimidazole (DRB). We show that PIP2 is associated with Pol I subunits and UBF in a transcription-independent manner. On the other hand, PIP2/fibrillarin colocalization is dependent on the production of rRNA. These results indicate that PIP2 is required not only during rRNA production and biogenesis, as we have shown before, but also plays a structural role as an anchor for the Pol I pre-initiation complex during the cell cycle. We suggest that throughout mitosis, PIP2 together with UBF is involved in forming and maintaining the core platform of the rDNA helix structure. Thus we introduce PIP2 as a novel component of the NOR complex, which is further engaged in the renewed rRNA synthesis upon exit from mitosis.
Keywords: Cell Cycle; nádorové buněčné linie; transcription; Nucleolus Organizer Region; PIP2; rekombinantní proteiny; HeLa Cells; mitóza; chromozomální proteiny, nehistonové; RNA Polymerase I; buněčné jadérko; Cell Line, Tumor; RNA-polymerasa I; DNA, Ribosomal; Transcription, Genetic; transkripční iniciační komplex Pol1 - proteiny; genetická transkripce; buněčný cyklus; Mitosis; fibrillarin; UBF; Humans; nucleolus; Pol1 Transcription Initiation Complex Proteins; ribozomální DNA; mitosis; Chromosomal Proteins, Non-Histone; RNA polymerase I; Cell Nucleolus; RNA ribozomální; RNA, Ribosomal; organizátor jadérka; HeLa buňky; lidé; Recombinant Proteins